EFFECTIVENESS OF MORINGA AND MACKEREL CAPSULES ON INCREASING HEMOGLOBIN LEVELS IN PREGNANT WOMEN IN THE WORKING AREA OF THE SINIU PUBLIC HEALTH CENTER, PARIGI MOUTONG REGENCY, CENTRAL SULAWESI - Retno Palupi Yonni Siwi; Niluh Devi Andewi (Journal for Quality in Women's Health, 2026)
The most common anemia encountered in pregnancy is iron deficiency anemia caused by insufficient intake of iron in food, impaired absorption, increased iron requirements. Anemia management in pregnant women by administering 90 Fe tablets during pregnancy. One of the foods that have good nutritional content for pregnant women is moringa leaves and mackerel. The purpose of this study was to analyze the effectiveness of moringa and mackerel capsules on increasing hemoglobin levels in pregnant women in the Siniu Community Health Center Work Area, Parigi Moutong Regency, Central Sulawesi. This study is a quantitative study, the method used is quasi-experimental, with a non-equivalent control group pretest post-test design with experimental and control groups. The sample of this study was pregnant women in the third trimester at the Siniu Community Health Center, Parigi Moutong Regency, Central Sulawesi with an intervention of 15 mothers given moringa capsules and 15 mothers given mackerel.